Destruction Mechanism and Kinetic of Formaldehyde by O3 and OH Radicals - Wen, Zhengcheng; Xu, Jiangrong; Wang, Zhihua; Zhou, Junhu; Cen, Kefa (Asian Journal of Chemistry, 2011)
The catalytic oxidation technology has been believed as the most promising technology of formaldehyde destruction because of its high efficiency, thorough destruction and easy application. For the catalytic oxidation technology, formaldehyde was radically destructed by the O3 and OH radicals, which were produced by various catalytic ways such as photo-catalysis and electrocatalysis. Due to its fundamental importance, the destruction mechanism of formaldehyde by O3 and OH radicals was investigated in detail by employing quantum chemical calculation in this work. The microcosmic reaction process was calculated and discussed in detail by the UB3LYP/6-31G(d) method and the activation energies were calculated by the QCISD(T)/6- 311g(d,p) method. Furthermore, the kinetic parameters were also calculated by the transition state theory. Theoretical results showed that the activation energies of the HCHO + OH reaction (3.57 kcal/mol) was much lower than that of the HCHO + O3 (20.20 kcal/mol) and the rate constant of the HCHO + OH reaction was much larger than that of the HCHO + O3 reaction. This indicated that the OH radical has much stronger ability to destruct formaldehyde than the O3 radical, which was in conformity with that the OH radical has much stronger oxidation character than the O3 radical. Moreover, by comparing, the theoretical results were in agreement with the experimental results in literature, which indicated the theoretical calculation in this work was reasonable and reliable.